2016
DOI: 10.9734/ajea/2016/22216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Selected Pigeonpea (Cajanus cajan (L.) Millsp.) Genotypes for Resistance to Insect Pest Complex in Dry Areas of North Rift Valley, Kenya

Abstract: Pigeonpea is an important pulse crop that has gained importance in semi-arid tropics, although its yield potential has not been fully realized due to biotic and abiotic stresses that limit its production. Insect pest complex of pod borer (Helicoverpa armigera), sucking bug (Clavigralla tomentosicollis) and pod fly (Melanagromyza cholcosoma) are the major limiting factors to its production causing up Original Research Article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…This also suggests that the varieties were more adapted to the micro-environment under strip intercropping to efficiently utilise the growth factors such as light, water, nutrients and space to produce more branches, pods, and a higher grain yield than the mixed intercropping. Similar significant variations in pigeonpea varieties for different yieldattributes were reported in previous studies (Cheboi et al 2016;Hardev 2016;Sujatha and Babalad 2018;Thanga et al 2019). In this study, three varieties (ICEAP 01101-2, ICEAP 00604, and ICEAP 001284) produced a higher number of primary branches, pods per plant, and higher grain yields during both seasons.…”
Section: Discussionsupporting
confidence: 87%
“…This also suggests that the varieties were more adapted to the micro-environment under strip intercropping to efficiently utilise the growth factors such as light, water, nutrients and space to produce more branches, pods, and a higher grain yield than the mixed intercropping. Similar significant variations in pigeonpea varieties for different yieldattributes were reported in previous studies (Cheboi et al 2016;Hardev 2016;Sujatha and Babalad 2018;Thanga et al 2019). In this study, three varieties (ICEAP 01101-2, ICEAP 00604, and ICEAP 001284) produced a higher number of primary branches, pods per plant, and higher grain yields during both seasons.…”
Section: Discussionsupporting
confidence: 87%
“…However, damage to the reproductive parts, particularly the flowers and developing seeds, results in direct yield and economic losses. To investigate the genotype-specific response to the pod borer infestation, we conducted an insect bioassay on the cultivated susceptible cultivar KAT 60/8 (CT) [ 26 ] and a resistant wild relative accession (WT) [ 5 ] using the whole plant and detached leaves assays. Four-week-old seedlings and detached leaves were subjected to H. armigera infestation for a period of 24 h. The results show severe defoliation in CT, while minimal leaf damage was observed on the wild relative seedlings under the whole plant and petri plate assays ( Figure 1 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…This may be contributed by presence of morphological traits or biochemical factors that influence selection or preference of pod borer among genotypes. Cheboi et al, 2016 reported potential yield among seven genotypes with low pod and seed damage. Similarly, Pod borer damage was high in Marigat (hotspot area) compared to other studied areas.…”
Section: Phenotypic Data On Mechanisms Of Pod Borer Resistancementioning
confidence: 99%